PROFIL MOTIVASI BELAJAR PESERTA DIDIK PADA PELAJARAN BIOLOGI KELAS XI IPA SMAN DI KABUPATEN SINJAI - Syamsul Syamsul; Abdul Rahim; Syahriani Syahriani; Herinda Mardin; A.S. Alonemarera (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
Students' learning motivation is the driving force they have and provides energy to carry out learning activities so that the continuity of learning can be directed and the desired goals can be realized. The purpose of this study was to describe the learning motivation of students in class XI IPA SMAN in the Sinjai Regency. This type of research is a descriptive survey with a population of 1267 students and a sample of 616 students taken by cluster random sampling technique. The instrument used is a student learning motivation questionnaire that has met the valid and reliable criteria with the measured aspects being diligent in facing tasks, tenacious in facing difficulties, showing interest, and being able to defend their opinions. The data analysis technique used is descriptive statistical analysis. The results of this study indicate that the learning motivation of students in class XI IPA SMAN in the Sinjai Regency there are 179 (29.1%) students in the medium category and 437 (70.9%) students in the high category. The results of the analysis indicate that the dominant learning motivation of students is in the high category which is certainly influenced by many factors.